First neonatal case of fungaemia due to Pseudozyma aphidis and a global literature review. Issue 1 (8th July 2013) - Prakash, Anupam; Wankhede, Sandeep; Singh, Pradeep K.; Agarwal, Kshitij; Kathuria, Shallu; Sengupta, Sharmila; Barman, Purabi; Meis, Jacques F.; Chowdhary, Anuradha
Summary: The Ustilaginomycetous basidiomycete yeast, Pseudozyma aphidis has recently been implicated in potentially fatal disorders ranging from subcutaneous mycoses to disseminated infections. Till date a solitary case of P. aphidis fungaemia in a paediatric patient has been reported. We present a case of fungaemia due to P. aphidis in a rhesus factor‐isoimmunised, low‐birth‐weight neonate. The isolate was identified by sequencing the D1/D2 domain of the LSU region. Antifungal susceptibility of the isolate revealed susceptibility to amphotericin B, voriconazole, itraconazole, isavuconazole and posaconazole. It had high minimum inhibitory concentrations of fluconazole and was resistant to flucytosine and echinocandins. Consequently, the patient was successfully treated with intravenous amphotericin B. Although the source of infection could not be traced, as the neonate developed fungaemia on the first day of life, it could possibly be from the maternal urogenital tract or intrahospital transmission. A review of previously published cases revealed that risk factors for invasive Pseudozyma spp. infections were similar to those previously reported for non‐ albicans Candida spp. Pseudozyma species are underreported due to the difficulty of identifying this rare yeast pathogen by commercial identification systems. Considering that Pseudozyma spp. cause invasive fungal infections globally and are resistant to flucytosine, fluconazole and echinocandins, this pathogen assumes a greater clinical significance.